Marine Geodesy - Marine Geodesy (Taylor & Francis, 2026)
The aim of Marine Geodesy is to stimulate progress in ocean surveys, mapping, and remote sensing by promoting problem-oriented research in the marine and coastal environment.
FI 0.51
Q2
Keywords: Biological; Earth & Environmental Food Science; Geodesia marina; Acuerdos transformativos; Transformative agreements; Entornos marinos y costeros; Cartografía; Batimetría; Teledetección; Navegación; Tectónica de placas; Instrumentación; Sistemas de Información Geográfica